2014
DOI: 10.1016/j.idcr.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Three cases of presumed pneumocystis pneumonia in patients receiving bortezomib therapy for multiple myeloma

Abstract: HighlightsThree patients receiving bortezomib therapy for multiple myeloma presented with clinical and radiological features consistent with PCP.The patients deteriorated whilst receiving broad-spectrum antibiotics but responded to sulfamethoxazole + trimethoprim.The negative sputum PCR results in two patients may be due to the prior initiation of sulfamethoxazole + trimethoprim and absence of BAL specimens.The three patients were receiving dexamethasone at doses and durations at the threshold expected to caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Limited data suggest the risk of PCP with bortezomib in multiple myeloma patients treated with high dose corticosteroids; however, the overall risk is low. 37,38 The incidence of PCP with TNF inhibitors, tocilizumab, and rituximab is also low; however, several studies have demonstrated that the risk of infection is increased in particular conditions including age >65 years, concurrent long-term corticosteroid use (e.g., ≥ 15 mg/day prednisolone for more than four weeks), and co-existence of either pulmonary diseases or underlying granulomatosis with polyangiitis. 38,39 Comparative studies have shown a greater risk with TNF inhibitors, particularly infliximab than tocilizumab.…”
Section: Bcr-abl Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…Limited data suggest the risk of PCP with bortezomib in multiple myeloma patients treated with high dose corticosteroids; however, the overall risk is low. 37,38 The incidence of PCP with TNF inhibitors, tocilizumab, and rituximab is also low; however, several studies have demonstrated that the risk of infection is increased in particular conditions including age >65 years, concurrent long-term corticosteroid use (e.g., ≥ 15 mg/day prednisolone for more than four weeks), and co-existence of either pulmonary diseases or underlying granulomatosis with polyangiitis. 38,39 Comparative studies have shown a greater risk with TNF inhibitors, particularly infliximab than tocilizumab.…”
Section: Bcr-abl Tyrosine Kinase Inhibitorsmentioning
confidence: 99%